Implementation of Mudharabah Contract on Foreign Currency Deposit Investment in Indonesian Islamic Banking - Farhan, Muhammad; Nawi, Syaruddin; Sahban, Sahban (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This study aims to determine and analyze the Implementation of Mudharabah Contract on Foreign Currency Deposits in Indonesian Islamic Banking Study at Bank Syariah Indonesia Makassar branch. This study was conducted with an empirical type that uses primary legal materials or is a study by going directly to the location. The results of this study indicate that Bank Syariah Indonesia Makassar branch has complied based on the Fatwa of the National Sharia Council No. 03 / DSN-MUI / IV / 2000 concerning deposits in Law No. 21 of 2008 concerning Indonesian Islamic Banking, namely collecting funds in the form of Investments in the form of Deposits, Savings, or other forms that are equated with it based on the Mudharabah Contract or other Contracts that do not conflict with Sharia Principles. Bank Syariah Indonesia Makassar branch has complied with existing laws, namely Sharia Banking Law No. 21 of 2008, and the National Sharia Council Fatwa No: 03/DSN-MUI/IV/2000 has complied with existing Sharia principles.